The Enlightenment : A brief history with documents - Jacob, Margaret C. (The Bedford series in history and culture, 2017)
Gain insight into The Enlightenment from the era's most influential thinkers as Enlightenment explores the impact this time period had on the political, religious, and educational landscape of the day.